Role of privacy/safety risk and trust on the development of prosumption and value co-creation under the sharing economy: a moderated mediation model. Issue 4 (2nd October 2021) - Shah, Syed Hamad Hassan; Noor, Saleha; Lei, Shen; Butt, Atif Saleem; Ali, Muhammad
ABSTRACT: Information technologies (ITs), including digital platforms and the Internet of things have dramatically supported prosumption behavior in value co-creation (VCC) development under the sharing economy perspective. However, privacy-safety risk (PSR) and prosumers' trust may significantly impact this transaction through digital platforms under the sharing economy. Therefore, this study examined the prosumption role as a mediator between PSR and VCC through a digital platform under the sharing economy. Moreover, the moderating role of prosumers' trust between prosumption and VCC has been explored. This study used quantitative methodology and data collected from Uber customers in Pakistan and DiDi customers in China. This study found that prosumption mediates the relationship between PSR and VCC and trust moderates the relationship between prosumption and VCC. This study portrays the influence of PSR and prosumers' trust factors to understand the prosumption and VCC relationship through a digital platform that provides a win-win outcome for customers and the company under the sharing economy perspective.